Epidemiological Studies On Interdigital Hyperplasia In Cattle In North Gujarat And Saurashtra Region Of Gujarat State. - Gosai, R. K.; Tank, P. H.; Parmar, B. N.; Thakkar , H. D. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The interdigital hyperplasia is an overgrowth of skin fold adjacent to axial hoof wall. It can occur in one or more limbs, although hind limb affected more frequently than forelimb (Singh and Singh, 1995). Dermatitis, poor claw conformation, incorrect claw trimming and interdigital phlegmon predispose cows to hyperplasia (Manske, 2002). The present study was undertaken to know the clinical epidemiological status of interdigital hyperplasia in cattle of North Gujarat and Saurashtra region of Gujarat State.